Tugas dalam Perkuliahan: Profil Prokrastinasi Akademik Mahasiswa Jurusan Tadris Biologi IAIN Kerinci - Ferry, Dharma; Vera, Yulda Hermi; Kamil, Dairabi (Pedagogi Hayati, 2022)
This study aims to determine how the academic procrastination of students at Biology Department of State Islamic Institute of Kerinci. This research was conducted on 189 students of the Biology Education of State Islamic Institute of Kerinci at the 2nd semester to the 8th semester who were randomly selected. The population in this study were students of the Biology Education at State Islamic Institute of Kerinci. Sample were selected by using by using the Slovin formula. Then, the sample obtained is 140 samples, while in this study the researchers took more than the number of samples that should be as many as 189 samples. While the sampling technique used by researchers is Simple Random Sampling. Based on the results of the research conducted by the author at the Biology Study Program of IAIN Kerinci, it was found that through a questionnaire distributed to 189 students, academic procrastination could be concluded that the academic procrastination of IAIN Kerinci Biology Department students was classified as high at 42.85% with a frequency of 81 respondents, with the average male gender which is higher that is equal to 80.2 on average. With academic procrastination, students of the Department of Biology Tadris IAIN Kerinci based on gender, the average is higher on male students.